Modelling of ash deposition in biomass boilers: a review. (December 2017) - Yongtie, Cai; Wenming, Yang; Zhimin, Zheng; Mingchen, Xu; Boon, Siah Keng; Subbaiah, Prabakaran
Abstract: The ash deposition process in biomass boilers can induce many ash-related problems. It will reduce the heat transfer in the furnace walls and convective pass tubes and decrease the boiler efficiency and capacity. Previous review work and experience about the ash deposition process was almost focusing on coal-fired utility boiler, providing an extensive summary of knowledge and current developments about ash deposition processes, but few was concentrating on the biomass fuel-derived boiler. Numeral empirical and traditional methods, such as ash fusibility, ash viscosity, and slagging and fouling indices, which are based on the temperature and the chemical compositions, cannot fully predict the complicated ash deposition processes. To understand the nature of ash deposition in biomass boilers, full attention should be paid to the ash deposition processes, including the transformation process of mineral matter in biomass fuels and deposition characteristics. To predict the ash deposition process, some ash deposition models, such as the ash transportation model, the ash formation model, the ash impacting model, the ash sticking model and the ash growth model, should be developed. This paper will give a brief introduction to the traditional methods about the ash deposition. In additional, an extensive state-of-the-art review of the ash deposition in biomass fuel-derived boiler will be presented. Lastly, the comprehensive ash deposition models including the mechanistic models and CFD modelling will be built to address the ash-related issues, which can guide further investigation.